Hadits sebagai Landasan Normatif dalam Ekonomi Islam Definisi, Urgensi, dan Aplikasinya - M. Yusuf Kusuma Wijaya; Ainur Rofiq Sofa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Hadith serves as one of the primary sources of Islamic law and plays a significant role in shaping various aspects of life, including the economic domain. As a normative foundation, Hadith not only complements the Qur’an but also provides practical guidance for the economic activities of Muslims. This study aims to explore the definition of Hadith in the context of Islamic economics, its urgency as a normative basis, and its application in contemporary economic practices. Employing a qualitative-descriptive approach and library research method, the study reveals that Hadith offers fundamental principles such as justice, honesty, prohibition of usury (riba), as well as encouragement for fair trade and hard work. The urgency of Hadith in Islamic economics is evident in its contribution to forming an economic system rooted in moral and spiritual values. Its application can be seen in practices such as zakat, Islamic contracts (muamalah), and Islamic business ethics. Thus, Hadith plays a central role in building an economic framework that is not only rational but also ethical and just.